Sales through blogs in Malaysia: should we regulate them? - Mohamed, Duryana (IAITL, 2014)
Selling goods through blogs is becoming a trend in Malaysia particularly for consumer goods. Goods like homemade chocolate, cup cakes, designed and personal accessories are among the many types of businesses which are commonly carried up via blogs. The popularity of blog sales give rise to legal concerns such as should these the blogs’ businesses be regulated as it is possible these blogs maybe mere bogus or scams or simply temporary in nature. What about the consumer rights arising from these transactions? This article will examine this issue from the Malaysian law perspective with some comparison with a heavily regulated jurisdiction like Singapore. (103 words)